2018
DOI: 10.1155/2018/4362101
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Vibration Control for AMB Flexible Rotor System Based onµ-Synthesis Controller

Abstract: The resonance vibration control of flexible rotor supported on active magnetic bearings (AMB) is a challenging issue in the industrial applications. This work addresses the application of robust control method to the resonance vibration control for AMB flexible rotor while passing through the critical speed. This model-based method shows great superiority to handling flexible mode vibration, which can guarantee robust stability and performance when encountering modal perturbation. First, the designed flexible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…2. Assuming that the unbalanced force of the rotor is supported by the left and right radial magnetic bearings, so the original unbalanced force on the rotor can be equivalent to the positions of the two active magnetic bearings by using the equivalent principle [6,7] . Therefore, the aim of controlling the unbalanced force of the rotor system can be achieved by restraining the equivalent unbalanced force of bearing position.…”
Section: Principle Of the Influence Coefficient Methodsmentioning
confidence: 99%
“…2. Assuming that the unbalanced force of the rotor is supported by the left and right radial magnetic bearings, so the original unbalanced force on the rotor can be equivalent to the positions of the two active magnetic bearings by using the equivalent principle [6,7] . Therefore, the aim of controlling the unbalanced force of the rotor system can be achieved by restraining the equivalent unbalanced force of bearing position.…”
Section: Principle Of the Influence Coefficient Methodsmentioning
confidence: 99%
“…A bridge circuit can control the current of one coil, but is not sufficient to control the motion of the rotor in one DOF. This is because the electromagnetic force has a strong nonlinear characteristic, so an AMB generally adopts differential control with two coils controlling one DOF motion [14], as shown in Figure 2, and the electromagnetic force can be linearized when the rotor is near the center position. Therefore, the complete suspension of the rotor requires two radial AMBs, as shown in Figure 1.…”
Section: Topologies Of Amb Amplifiersmentioning
confidence: 99%
“…For the vibration control of flexible and long rotors, an experimental and theoretical analysis is carried out in [9], and the multivariable nature of controllers is emphasized in [10]. Moreover, it has been shown that there exist controllers that suppress vibrations at resonance [11].…”
Section: Introductionmentioning
confidence: 99%